An epidemiological study of period poverty among females of reproductive age group in Lucknow (U.P.) - Swati Singh; Rajesh Kunwar; Mili Sengar; Abhishek Gupta (Journal of Family Medicine and Primary Care, 2023)
Background: Females in developing countries face brunt of lack of access to affordable menstrual supplies and inequitable distribution of menstrual health education and are victims of period poverty. The objective of the present study was to estimate prevalence of period poverty and to determine association of period poverty with socio-demographic determinants, menstrual knowledge, menstrual hygiene management practices, and reproductive health. Materials and Methods: This was an analytical cross-sectional study, conducted at an urban primary health care centre. Reproductive age group (20–49 years) females attending the primary health care centre from December 2022 to May 2023 were selected for study. Data were collected on semi-structured, pre-tested questionnaires. The collected data were entered in M.S Excel and analysed in STATA version 17.0. Chi-square test was used for comparison of qualitative data, and for quantitative data, unpaired t-test was used. Results: The prevalence of period poverty in the present study was 92 (29.7%). The mean age of females with period poverty was 29.72 ± 7.13 years, and it was 26.45 ± 6.62 years with no period poverty (P 0.001). Period poverty was significantly associated with socio-demographic variables. Period poverty had significant association with menstrual knowledge, menstrual hygiene management practices, and reproductive health. Conclusion: Many females cannot afford menstrual health products to meet their monthly needs, and this may affect their education and socio-economic status. Improved access to affordable sanitary products is requisite of females.